(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research delves into the transformative role of emerging technologies like AI, biotechnology, and space exploration. It examines their contributions to governance, healthcare, and education in building a prosperous nation.